To Determine the Efficacy and Safety of TAP Block with Versus Without Buprenorphine in Managing Postoperative Pain Following Inguinal Hernia Repair - Rathod, Anil (Journal of Biomedical and Pharmaceutical Research, 2021)
Background: The Transversus Abdominis Plane (TAP) block is a widely used regional anesthesia technique for managing postoperative pain in patients undergoing inguinal hernia repair. The addition of buprenorphine, a long-acting opioid, to the TAP block may enhance the duration and quality of analgesia. This study aims to evaluate the impact of this combination on postoperative pain management following inguinal hernia repair. By comparing TAP blocks with and without buprenorphine, we seek to determine whether the addition of buprenorphine enhances analgesia, reduces opioid consumption, and improves overall patient outcomes. This study will contribute valuable information to the field of postoperative pain management, potentially leading to more effective and safer analgesic strategies for patients undergoing inguinal hernia repair. The addition of buprenorphine, a long-acting opioid, to the TAP block may enhance the duration and quality of analgesia. Aim: This study aims to determine the efficacy and safety of TAP block with versus without buprenorphine in managing postoperative pain following inguinal hernia repair. Material and Method: This study is a prospective, randomized, double-blind clinical trial designed to evaluate the efficacy of TAP block with or without buprenorphine in managing postoperative pain following inguinal hernia repair experimental study conducted in the Department of General Surgery. Patients were recruited from Department of Surgery. This study involves 50 patients undergoing inguinal hernia surgery. Group A of 25 patients contained TAP block with buprenorphine and Group B of 25 patients contained TAP block without buprenorphine. Primary objective of the study was to evaluate the effect of TAP block with or without buprenorphine on patients undergoing inguinal hernia repair.